Pengaruh Kinerja Keuangan dan Financial leverage Terhadap Financial Distress Pada Perusahaan Consumer Cyclicals yang Terdaftar di Bursa Efek Indonesia Periode 2020-2022 - Syavira, Adhelia; Metalia, Mega; Oktavia, Reni; Desriani, Neny (Jurnal EMT KITA, 2024)
This research aims to find out whether financial performance and financial leverage influence financial distress in consumer cyclical companies listed on the Indonesia Stock Exchange for the 2020-2022 period. This study uses a quantitative approach. The population in this study is the population in this study is the Consumer Cyclicals company listed on the Indonesia Stock Exchange for the 2020-2022 period. The sampling technique in this research used a purposive sampling method. The results of this research show that financial performance has a negative effect on financial distress in consumer cyclical companies. The results of this research show that the first hypothesis (H1) is supported and financial leverage has a negative effect on financial distress in consumer cyclical companies. The research results show that the second hypothesis (H2) is not supported.